Text Mining of Unstructured Data Using R - Siva Lakshmi, M; Arsha Sultana, MD (International Journal of Computer Sciences and Engineering, 2025)
Text mining is the process of acquiring high-quality information from text that is typically borrowed through the devising of patterns and trends such as statistical pattern learning .It usually involves the process of structuring the input text, deriving patterns within the structured data and finally evaluation and interpretation of the output. It can help an organization to acquire potentially valuable business insights from text-based content such as word documents, email and postings on social media streams like Facebook, Twitter and LinkedIn. Mining unstructured data with natural language processing (NLP), statistical modeling and machine learning techniques can be challenging because natural language text is often inconsistent. So, R is used to mine unstructured data which is the most exhaustive statistical analysis package and it incorporates all of the standard statistical tests, models and analyses for managing and manipulating data.